Discovery of small molecule inhibitors of xyloglucan endotransglucosylase (XET) activity by high-throughput screening. (September 2015) - Chormova, Dimitra; Franková, Lenka; Defries, Andrew; Cutler, Sean R.; Fry, Stephen C.
Abstract : Graphical abstract: Xenobiotics that inhibit the cell-wall-remodelling enzyme activity, xyloglucan endotransglucosylase (XET), would be a valuable tool in 'chemical genetics' for elucidating its biological roles. By screening 4216 small molecules in a dot-blot assay on paper-immobilised xyloglucan, we discovered 45 compounds that inhibited or promoted XET activity. The most effective inhibitors were singlet oxygen generators. Highlights: We screened chemical collections for XET modulators in filter-paper-based dot-blot assays. Some 'hits' inhibited, others promoted, XET activity on cellulose-bound xyloglucan. Most of the promoters inhibited XET when re-assayed radiochemically on soluble xyloglucan. The strongest XET inhibitors were singlet oxygen-generators e.g., riboflavin (IC50 29 μM). XET inhibitors are potentially useful as tools for probing XET's roles in vivo . Abstract: Small molecules (xenobiotics) that inhibit cell-wall-localised enzymes are valuable for elucidating the enzymes' biological roles. We applied a high-throughput fluorescent dot-blot screen to search for inhibitors of Petroselinum xyloglucan endotransglucosylase (XET) activity in vitro . Of 4216 xenobiotics tested, with cellulose-bound xyloglucan as donor-substrate, 18 inhibited XET activity and 18 promoted it (especially anthraquinones and flavonoids). No compounds promoted XET in quantitative assays with (cellulose-free) soluble xyloglucan as substrate, suggesting that promotion was dependent on enzyme–cellulose interactions. With cellulose-free xyloglucan as substrate, we found 22 XET-inhibitors – especially compounds that generate singlet oxygen ( 1 O2 ) e.g., riboflavin (IC50 29 μM), retinoic acid, eosin (IC50 27 μM) and erythrosin (IC50 36 μM). The riboflavin effect was light-dependent, supporting 1 O2 involvement. Other inhibitors included tannins, sulphydryl reagents and triphenylmethanes. Some inhibitors (vulpinic acid and brilliant blue G) were relatively specific to XET, affecting only two or three, respectively, of nine other wall-enzyme activities tested; others [e.g. (−)-epigallocatechin gallate and riboflavin] were non-specific. In vivo, out of eight XET-inhibitors bioassayed, erythrosin (1 μM) inhibited cell expansion in Rosa and Zea cell-suspension cultures, and 40 μM mycophenolic acid and (−)-epigallocatechin gallate inhibited Zea culture growth. Our work showcases a general high-throughput strategy for discovering wall-enzyme inhibitors, some being plant growth inhibitors potentially valuable as physiological tools or herbicide leads.